2021
DOI: 10.3390/cancers13061408
|View full text |Cite
|
Sign up to set email alerts
|

A MAPK/miR-29 Axis Suppresses Melanoma by Targeting MAFG and MYBL2

Abstract: The miR-29 family of microRNAs is encoded by two clusters, miR-29b1~a and miR-29b2~c, and is regulated by several oncogenic and tumor suppressive stimuli. While in vitro evidence suggests a tumor suppressor role for miR-29 in melanoma, the mechanisms underlying its deregulation and contribution to melanomagenesis have remained elusive. Using various in vitro systems, we show that oncogenic MAPK signaling paradoxically stimulates transcription of pri-miR-29b1~a and pri-miR-29b2~c, the latter in a p53-dependent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“… Koynovaa et al (2007) found a higher frequency of low-level increase of the copy numbers of MYBL2 rather than amplification in melanoma. Also, evidence showed that attenuation of miR-29b2∼c expression promotes the development of melanoma by partly depressing MAFG and MYBL2 ( Vera et al, 2021 ). Taken together, this evidence indicated that MYBL2 was involved in cell proliferation and tumorigenesis in melanoma, which is consistent with our present findings.…”
Section: Discussionmentioning
confidence: 99%
“… Koynovaa et al (2007) found a higher frequency of low-level increase of the copy numbers of MYBL2 rather than amplification in melanoma. Also, evidence showed that attenuation of miR-29b2∼c expression promotes the development of melanoma by partly depressing MAFG and MYBL2 ( Vera et al, 2021 ). Taken together, this evidence indicated that MYBL2 was involved in cell proliferation and tumorigenesis in melanoma, which is consistent with our present findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report the establishment of another 4 murine melanoma cell lines and the systematic characterization of key features for the 21 cell lines. Furthermore, by inducible CRISPR/Cas9-mediated depletion of MAFG, a transcription factor we recently identified as a potential vulnerability of melanoma ( Vera et al., 2021 ), we show the utility of the integrated regulatory elements for the characterization of genes of interest.…”
Section: Introductionmentioning
confidence: 76%
“…On Dox treatment, GFP expression was reduced ( Figure 6 b), thus validating Cas9 activity. To demonstrate the utility of Dox-inducible TRE-Cas9, we delivered a sgRNA targeting Mafg to two murine melanoma lines, a transcription factor we recently found to be important for the proliferation of melanoma cells ( Vera et al., 2021 ) ( Figure 6 a). Dox treatment reduced Mafg expression in TRE-Cas9 melanoma lines harboring a Mafg -targeting sgRNA ( Figure 6 c).…”
Section: Resultsmentioning
confidence: 99%
“…However, only MYBL2 is ubiquitously expressed in proliferating cells (12,13). The expression of MYBL2 gene is controlled by other transcription factors or noncoding RNA (41)(42)(43)(44)(45), and the MYBL2 protein is activated via phosphorylation (14,21). After activated, MYBL2 regulates downstream diverse genes or proteins involved in multiple cellular processes, such as BCL2 and MYC in cell survival (46)(47)(48), cyclins and FGF4 in cell cycle (49-51), SOX2 and OCT4 in cell differentiation (52,53), SNAIL and YAP1 in cell invasion and metastasis (19,54).…”
Section: Discussionmentioning
confidence: 99%